Bio‐Based Nanofiber Membranes for Effective Air Filtration: Fabrication and Evaluation of Flame‐Retardant Behavior, Mechanical Properties, and Filtration Performance - Sepideh Keyvani; Farideh Golbabaei; Rasoul Esmaeely Neisiany; Oisik Das; Abbas Rahimi Foroushani; Saba Kalantary (Macromolecular Materials and Engineering)
Abstract Electrospun nanofibers can lower health risks linked to exposure to particulate matter pollutants. On the other hand, nonbiodegradable polymeric materials increase issues related to their disposal and the generation of hazardous microplastics. Hence, this research aims to develop a nanofibrous membrane filter composed of polyvinyl alcohol (PVA) as a biodegradable polymer, and boric acid (BA) using an electrospinning technique. This study investigates the effect of BA on fire behavior, mechanical properties, and filtration performance of the nanofiber membranes. The morphological results show that the samples containing BA have no beads on the nanofibers. Incorporating boric acid into PVA membranes can reduce peak release heat by ≈39%. Additionally, the nanofibers containing BA can offer enhanced mechanical properties of tensile strain (≈3.6%) and Young's modulus (up to ≈45%). The optimized BA/PVA nanofibers can also demonstrate superior filtration efficiency (above 99.9% for 300 nm particles) and a low‐pressure drop (150 Pa at 5.3 cm s−1 airflow velocity). Therefore, PVA nanofibers containing BA can improve not only the fire behavior than those of pure PVA nanofibers, but also increase mechanical properties, and filtration performance.